2017
DOI: 10.1139/bcb-2016-0088
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and cell penetrating effects of LFcin17–30, LFampin265–284, and LF chimera on enteroaggregative Escherichia coli

Abstract: Lactoferrin (LF) is a protein with antimicrobial activity, which is conferred in part by 2 regions contained in its N-terminal lobe. These regions have been used to develop the following synthetic peptides: lactoferricin17–30, lactoferrampin265–284, and LF chimera (a fusion of lactoferricin17–30 and lactoferrampin265–284). We have reported that these LF peptides have antibacterial activity against several pathogenic bacteria; however, the exact mechanism of action has not been established. Here, we report the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 39 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Moreover, the results of SEM analysis showed that cLFchimera had no visible damaging effect on the outer layer of the bacteria, suggesting that maybe a molecular-level mechanism plays an important role in the synergistic action of cLFchimera. In this regards, Reyes-Cortes et al, (2017) showed that this chimeric peptide mediated its antibacterial activity by entering the cytoplasm through translocation across the bacterial membrane and possibly interacting with internal organelles [33]. Consistent with these results, Pirkhezranian et al, (2020 a, b) using molecular simulation analysis showed that cLFchimera and its derivatives had a higher a nity for DNA interaction and hypothesized this chimeric peptide mediated its activity by intramolecular mechanisms which interference DNA related pathways such as DNA replication [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of SEM analysis showed that cLFchimera had no visible damaging effect on the outer layer of the bacteria, suggesting that maybe a molecular-level mechanism plays an important role in the synergistic action of cLFchimera. In this regards, Reyes-Cortes et al, (2017) showed that this chimeric peptide mediated its antibacterial activity by entering the cytoplasm through translocation across the bacterial membrane and possibly interacting with internal organelles [33]. Consistent with these results, Pirkhezranian et al, (2020 a, b) using molecular simulation analysis showed that cLFchimera and its derivatives had a higher a nity for DNA interaction and hypothesized this chimeric peptide mediated its activity by intramolecular mechanisms which interference DNA related pathways such as DNA replication [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Although the intracellular activity of Lactoferrin derived peptides has been previously demonstrated [ 8], the exact mechanism of action has not been yet established. As recognition of specific DNA sequences by proteins is highly complex, involving structural, energetic and dynamic aspects, the interaction cannot be easily characterized at the atomic level by experimental approaches alone [ 16].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that a camel Lactoferrin chimera (CLFchimera) resulting from the fusion of the C-terminal ends of camel Lactoferricin 17-30 (CLFcin) and camel Lactoferrampin 265-284 (CLFampin) using the side chain of lysine as linker to the second peptide, has a broad-spectrum activity against both Gram-positive and Gram-negative bacteria [ 6,7]. Furthermore, Reyes-Cortes et al (2016) showed that this chimeric peptide mediated its antibacterial activity by entering the cytoplasm and possibly interacting with internal organelles [ 8]. To date, there has been no precise explanation for the mechanisms underlying the antimicrobial peptide function, but it is known that DNA is one of the most important intracellular targets for AMPs [ 9].…”
Section: Introductionmentioning
confidence: 99%
“…Lfcin (17-30) has been identified to act against bacteria, fungi, amoeba, stimulants of bio-warfare agents, and even bacterial biofilms (van der Kraan et al, 2005;Xu et al, 2010;Sijbrandij et al, 2017;Acosta-Smith et al, 2018;Díaz-Godínez et al, 2019). Nevertheless, its use against MDR pathogens, such as EAEC, remains unrevealed, barring a few systematic studies against pathogens like Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii (Reyes-Cortes et al, 2016;Pollini et al, 2017). Even studies addressing the antimicrobial and antibiofilm potential of Lfcin (17-30) against MDR-EAEC are lacking.…”
Section: Introductionmentioning
confidence: 99%